2009
DOI: 10.1007/s00259-009-1175-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited value of 18F-FDG PET/CT and S-100B tumour marker in the detection of liver metastases from uveal melanoma compared to liver metastases from cutaneous melanoma

Abstract: FDG PET/CT and serum S-100B are not sensitive enough for the detection of liver metastases from UM, whereas liver metastases from cutaneous melanoma are reliably FDG positive and lead regularly to increased S-100B tumour markers. The reason for the lower FDG uptake in UM liver metastases remains unclear. We recommend to perform combined contrast-enhanced PET/CT in order to detect FDG-negative liver metastases from UM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 37 publications
1
37
0
3
Order By: Relevance
“…There were 9 lesions measuring less than 5 mm in diameter, and none of these were detected by either test. Strobel et al 17 found that 41% of 27 hepatic metastases from uveal melanoma were FDG-positive as compared with 100% of 43 hepatic metastases from cutaneous melanoma. Feinstein et al reported 91 patients who underwent a CT scan within a month of uveal melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…There were 9 lesions measuring less than 5 mm in diameter, and none of these were detected by either test. Strobel et al 17 found that 41% of 27 hepatic metastases from uveal melanoma were FDG-positive as compared with 100% of 43 hepatic metastases from cutaneous melanoma. Feinstein et al reported 91 patients who underwent a CT scan within a month of uveal melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…With high sensitivity and spatial resolution, positron emission tomography (PET) has emerged as a powerful imaging technique for such purpose. While 2-[ 18 F]Fluorodeoxyglucose PET coupled with computed tomography (CT) is highly accurate in detecting metastatic disease in cutaneous melanomas 6, this modality lacks sensitivity for early nodal metastases, and liver metastases in uveal melanomas 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be stressed that no intravenous contrast media was used in the study mentioned, which might reduce the diagnostic performance of PET/CT; nevertheless, maximum standardized uptake value from uveal melanoma was significantly lower compared with hepatic metastases from cutaneous melanoma. 107 Although several authors report on a good performance of PET/CT in liver staging of uveal melanoma, 108,109 studies comparing PET/CT with liver MRI came to the conclusion that liver MRI is superior compared with PET/CT especially for small lesions. 110,111 Hybrid Imaging and Therapy Assessment in the Era of Targeted Therapies In the years gone by, new targeted therapies were introduced in the treatment of metastatic melanoma: with ipilimumab, a T-lymphocyte antigen-4 (CTLA-4) antibody, PD-1/PD-L1 antibodies such as nivolumab and lambrolizumab, and BRAF kinase inhibitors such as vemurafenib and dabrafenib as promising new substances are available.…”
Section: Noncutaneous Melanomamentioning
confidence: 98%